Usage Of Meme As Information Sharing Media - Tony Wibowo; Elvin (JURNAL ILMIAH BETRIK : Besemah Teknologi Informasi dan Komputer, 2020)
Internet Meme is one of many internet sub-culture and one of the most popular among millennials. This study aims to determine the use of memes in sharing information and entertainment at the same time. This research will require data in the form of student responses. Questions given to students that will relate to motives for seeking information, motives for entertaining, motives for maintaining relationships, continuous use and intentions in sharing information. This research was tested using the SPSS application from the data that had been collected. The final data that has been tested on Continuance Usage Intentions (CUI = 0.128) yields that the Information Seeking Motive (ISM = 0.344), the Entertainment Motive (EM = 0.350) and the Relationship Maintenance Motive (RMM = 0.247) have a close relationship. Meanwhile, the Information Sharing Intentions (ISI = -0.201) has a Information Seeking Motive (ISM = 0.379), Entertainment Motive (EM = 0.202) and Relationship Maintenance Motive (RMM = 0.410) which also has a close relationship. We can conclude that netizen are more concerned with entertainment motive and information seeking motive on continuance usage intentions which also netizen are concerned to information seeking motive and relationship maintenance motive on information sharing intention.